2022
DOI: 10.1515/ract-2021-1134
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigation of the different complexation and extraction properties of diastereomeric diglycolamide ligands

Abstract: (2R,2′S)-2,2′-oxybis-(N,N-didecylpropanamide) (cis-mTDDGA) and (2R,2′R)-2,2′-oxybis-(N,N-didecylpropanamide) (trans-mTDDGA) were studied using time-resolved laser fluorescence spectroscopy (TRLFS), vibronic side-band spectroscopy (VSBS) and density functional theory calculations (DFT) to find reasons for their different extraction properties. Stability constants of the respective Cm(III) and Eu(III) complexes show cis-mTDDGA to be the superior ligand which is in agreement with results from extraction experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These emission bands correspond to [Cm(TEDGA)] 3+ , [Cm(TEDGA) 2 ] 3+ , and Cm(TEDGA) 3 ] 3+ . The distinctive characteristics of these narrow emission bands and their maxima are consistent with those found in diglycolamide complexes in the existing literature [3a,6b,10] . The measured emission spectrum represents a superposition of individual Cm(III) species.…”
Section: Resultssupporting
confidence: 88%
“…These emission bands correspond to [Cm(TEDGA)] 3+ , [Cm(TEDGA) 2 ] 3+ , and Cm(TEDGA) 3 ] 3+ . The distinctive characteristics of these narrow emission bands and their maxima are consistent with those found in diglycolamide complexes in the existing literature [3a,6b,10] . The measured emission spectrum represents a superposition of individual Cm(III) species.…”
Section: Resultssupporting
confidence: 88%
“…This was added to the evaporation residue of the 243 Am­(OTf) 3 solution containing 1 mg of 243 Am­(III). The solution was then transferred into a J. Young-type NMR tube. …”
Section: Methodsmentioning
confidence: 99%
“…Short explanations were only given at the molecular scale. Finally, a major step forward was done with the works of Wilden and Weßling who showed that diastereoisomerism of some chiral diglycolamide (DGA) derivatives (Figure 13C) could significantly affect the organization of the ligand and its interaction with other partners than the metal cation (lanthanide or actinide), on the inner-and the outer-sphere of coordination [122,123].…”
Section: A Foreword About Significance Of the Stereoisomerism In The ...mentioning
confidence: 99%